A New Approach for Finding the Shortest path in Z-Graph Using Modifiers - P. Vijayalakshmi; Dr. G. Velammal (Utilitas Mathematica, 2025)
In this paper, we transform the Z-shortest path problem (ZSPP) into a fuzzy shortest path problem (FSPP) by applying the modifiers technique proposed by Shahila Bhanu M [7]. Then the fuzzy shortest path problem can be solved using suitable existing methods.